PERAN POPULASI CACING TANAH UNTUK PERBAIKAN SIFAT BIOFISIK TANAH PADA BERBAGAI SISTEM AGROFORESTRI BERBASIS KOPI DI BANGELAN, JAWA TIMUR - Nina Dwi Lestari; Raihan Habib; Ieke Wulan Ayu; Kurniawan Sigit Wicaksono; Nisfi Fari’atul Ifadah (LPPM Universitas Samawa, 2025)
Earthworms play a crucial role in improving the biophysical quality of soil by enhancing aeration, porosity, and nutrient availability. However, their population is highly influenced by soil depth and the type of shade plant. This study aimed to explore the relationship between fine root development, earthworm density, and soil physical properties under different shade types in the coffee plantation of PTPN 1 Bangelan, which has experienced productivity decline due to poor soil conditions. The research was conducted from September 2024 to February 2025 across five coffee land blocks with varying shade types (sengon, lamtoro, jabon, clove, and no shade), using a Randomized Complete Block Design (RCBD) with three replications. Soil samples were collected at two depths (0–30 cm and 30–60 cm). The results indicated that shade type significantly affected earthworm density, fine root growth, and soil physical properties. Lamtoro provided the best results, increasing earthworm density by 27,5% (0–30 cm) and 20,51% (30–60 cm), along with a significant increase in total root length and specific root length. Earthworm density also showed a positive contribution to improved soil physical properties, including increased porosity (6,24%), total root length (53,64%), and specific root length (18,09%), as well as reduced bulk density (7,54%) and soil penetration resistance (24,37%). These findings highlight the importance of selecting appropriate shade plants—particularly lamtoro—to support sustainable coffee land management by enhancing soil biophysical quality.